(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This paper discusses the eastern political and geographical de- mand for global empire —especially regarding the Western Mediterranean— from the neo-Assyrian kings to Alexander and the following western demand for global empire by the imitators of Alexander, i.e. from Hannibal, Pompey to the later-empire-rulers in Rome.